ANALISIS DAN STRATEGI PENGELOLAAN HUTAN TANAMAN INDUSTRI DI AREAL PT. SATRIA PERKASA AGUNG - Rika Az Zahrawani; Usman M Tang; Suwondo Suwondo (Program Pascasarjana Universitas Riau, 2015)
ABSTRACTThis study aimed to determine changes in the characteristics fisika aspects, chemical and biological propertiesof peat soil as a result of the activities of industrial timber estates at differentages, namely land use HTI age of 3 years, HTIHTI aged 4 years and 5 years of age and strategize Industrial Plantation Forest management. The results showed physical changes due to peatland conversion into Industrial Plantation Forestisan increase in the value of bulk density, particle density, water levels, chemical changes due to peatland conversion into Industrial Plantation Forestisan increase in the pH value and the content of C-organic, biological changes due to peatland conversion into Industrial Plantation Forestisa decrease inthe number of microbes. Results of the analysis strategy SWOTPT. Satria Agung Perkasa is inquadrant 1, with rekomedasi strategy, namely: Increase the commitment of all stakeholders in the management of peatland in accordance with prevailing regulations, Organize and manage the optimal conditions of water management, Invites all parties to be more concerned about the environmental impact monitoring peatland, Campaign on the importance of the role and maintain the condition of peat, and to promote the importance of the role and maintain the condition of peat.